Development of Attitudes of Members of Lithuanian Educational Community Towards Educational Reform - Želvys, Rimantas (Acta Paedagogica Vilnensia, 2001)
In 1996 and 1999 two opinion surveys were conducted in order to find out what were the attitudes of members of Lithuanian educational community towards the ongoing educational reform. Educational leaders of different levels in 1996 and beginning teachers in 1999 were interviewed by using the same questions of the opinion questionnaire. The aim of the article is to com pare the data acquired during both surveys. Results revealed similarity of outlooks expressed by respondents who were interviewed during both surveys. Majority of the interviewed members of Lithuanian educational community think that the start of educational reform was medium in the degree to which it was successful; they evaluate the present situation in education as satisfactory and express optimistic outlook towards the future. Majority of investigatives consider the present educational system better than the Soviet one. Most of the respondents support the main direction of the reform and consider their participation as medium in terms of their activity. They think that the present educational reform is more a „top-down" than a „bottom-up" one; its pace is medium, and the aims are broad. The only difference between the surveys of 1996 and 1999 was revealed while answering the question about the personal situation. In 1996 most of the respondents indicated that their personal situation has improved, while in 1999 majority of investigatives claimed that it has not changed. We think that it is due to the different experience and status of the two groups: educational leaders managed to gain more from educational reform than the beginning teachers. The findings also indicate the need for further periodical research of attitudes among Lithuanian educators about the ongoing educational reform.